Real World Data in Adaptive Biomedical Innovation: A Framework for Generating Evidence Fit for Decision‐Making. Issue 6 (19th October 2016) - Schneeweiss, S; Eichler, H‐G; Garcia‐Altes, A; Chinn, C; Eggimann, A‐V; Garner, S; Goettsch, W; Lim, R; Löbker, W; Martin, D; Müller, T; Park, BJ; et al.
Abstract : Analyses of healthcare databases (claims, electronic health records [EHRs]) are useful supplements to clinical trials for generating evidence on the effectiveness, harm, use, and value of medical products in routine care. A constant stream of data from the routine operation of modern healthcare systems, which can be analyzed in rapid cycles, enables incremental evidence development to support accelerated and appropriate access to innovative medicines. Evidentiary needs by regulators, Health Technology Assessment, payers, clinicians, and patients after marketing authorization comprise (1) monitoring of medication performance in routine care, including the materialized effectiveness, harm, and value; (2) identifying new patient strata with added value or unacceptable harms; and (3) monitoring targeted utilization. Adaptive biomedical innovation (ABI) with rapid cycle database analytics is successfully enabled if evidence is meaningful, valid, expedited, and transparent. These principles will bring rigor and credibility to current efforts to increase research efficiency while upholding evidentiary standards required for effective decision‐making in healthcare.